Comparison of Approaches to Revascularization in Patients With Multivessel Coronary Artery Disease Presenting With ST‐Segment Elevation Myocardial Infarction: Meta‐analyses of Randomized Control Trials. Issue 12 (December 2015) - Bajaj, Navkaranbir S.; Kalra, Rajat; Aggarwal, Himanshu; Ather, Sameer; Gaba, Saurabh; Arora, Garima; McGiffin, David C.; Ahmed, Mustafa; Aslibekyan, Stella; Arora, Pankaj
Abstract : Background: Significant controversy exists regarding the best approach for nonculprit vessel revascularization in patients with multivessel coronary artery disease presenting with ST‐segment elevation myocardial infarction. We conducted a systematic investigation to pool data from current randomized controlled trials (RCTs) to assess optimal treatment strategies in this patient population. Methods and Results: A comprehensive search of SCOPUS from inception through May 2015 was performed using predefined criteria. We compared efficacy and safety outcomes of different approaches by categorizing the studies into 3 groups: (1) complete revascularization (CR) versus culprit lesion revascularization (CL) at index hospitalization, (2) CR at index hospitalization versus staged revascularization (SR) of nonculprit vessels at a separate hospitalization, and (3) comparison of SR versus CL. Eight eligible RCTs met the inclusion criteria: (1) CR versus CL (6 RCTs, n=1727) (2) CR versus SR (3 RCTs, n=311), and (3) SR versus CL (1 RCT, n=149). We observed significantly lower rates of major adverse cardiovascular events, revascularization, and repeat percutaneous coronary interventions among patients treated with CR and SR compared with a CL approach ( P <0.05). The rates of all‐cause mortality, cause‐specific mortality, major bleeding, reinfarction, stroke, and contrast‐induced nephropathy did not differ in the CR arm compared with the CL arm. The rates of these outcomes were similar in the CR and SR arms. Conclusion: Results suggest that CR and SR compared with CL reduce major adverse cardiovascular event and revascularization rates primarily by lowering repeated percutaneous coronary intervention rates. We did not observe any increase in the rate of adverse events while using a CR or SR strategy compared with a CL approach. Current guidelines discouraging CR need to be reevaluated, and clinical judgment should prevail in treating multivessel coronary artery disease patients with ST‐segment elevation myocardial infarction as data from larger RCTs accumulate.